RELATIONS OF LEADERSHIP AND EMPLOYEE MOTIVATION WITH EMPLOYEE PERFORMANCE OF EMERGENCY INSTALLATION - Roza Asnel; Rahmawati Rahmawati (Jurnal Keperawatan Abdurrab, 2017)
RELATIONS OF LEADERSHIP AND EMPLOYEE MOTIVATION WITH EMPLOYEE PERFORMANCE OF EMERGENCY INSTALLATION Everyone's performance within the organization is influenced by leadership and motivation. Leadership is a gateway to both personal and organizational effectiveness. Leaders need to consider efforts to motivate employees to work well. Data in arifin ahmad showed an increase in the number of employees who are absent without explanation in June of 42.89 % , juli 34.87 % , 53.14 % in August 2014 from 55 employees . This study aims to determine the relations of leadership and employee motivation with employee performance of emergency installation . This study is a quantitative research with cross sectional study conducted from November 2015- February 2016. The sample consisted of 55 respondents selected by Total Sampling . The variables studied were leadership and motivation . The data collection was done by using a questionnaire filled out by workers. The data obtained will be processed by univariate and bivariate.The results showed that there is a significant relationship between employee performance variables leadership P value 0,00 < 0.05 ; POR ( CI = 95 % ) = 34.50 (7,704-154,5) , motivation p value 0,00 < 0.05 ; POR ( CI = 95 % ) = 10.92 (3,062-38,97) .Suggested to emergency installation to maintain and provide good cooperation between leaders and employees and always provide motivation among employee to improving employee performance .